Penerapan Akuntansi Perbankan Syariah untuk Produk Pembiayaan Murabahah Berdasarkan PSAK No 102 Tentang Akuntansi Murabahah ( Studi Kasus Pada KSPPS BMT Lumbung Artho Jepara) - Avita Yuliana; Ali Sofwan (Accounting Study Program, Faculty of Economics and Business, 2018)
PSAK No. 102 is an accounting system that looks at the recording process of financing products using a buying and selling system from the transaction process between the parties involved into the accounting system used in Islamic banking institutions. In line with this, the financing product at KSPPS BMT LUMBUNG ARTHO JEPARA is murabahah financing. The formulation of the problem in this research is how to apply PSAK No. 102 concerning Accounting for Murabahah Financing at KSPPS BMT LUMBUNG ARTHO JEPARA and whether its implementation is in accordance with Statement of Financial Accounting Standards (PSAK) No. 102. This study aims to determine the application of murabahah financing applied by KSPPS BMT LUMBUNG ARTHO JEPARA and whether the application is in accordance with the Statement of Financial Accounting Standards (PSAK) No. 102. The type of research is qualitative research, data collection using interview techniques and literature study. The results of this study indicate that the application of murabahah financing applied by KSPPS BMT LUMBUNG ARTHO is in accordance with the Statement of Financial Accounting Standards (PSAK) No. 102. The conclusion of this study shows that the application of murabahah financing at KSPPS BMT LUMBUNG ARTHO in the form of pricing, determining muarabahah assets, determining discounts is in accordance with PSAK No. 102 regarding Murabaha.